(untitled) (ModaPalavra e-periódico, 2011)
After the Haute Couture, abandonment of handmade clothing and tailors, and the beginning of the Prêt-à-porter fashion has gone through several transformations; some of them are; the development of production techniques, new technologies, new materials and also introducing important products in everyday. The trend has created wealth, put the textile industry and designers in the spotlight. this process involves psychological, sociological and financial aspects and it incorporates the needs and desires of consumers. In the XXI century, the analysis of this whole production chain encompasses the sustainable aspects. From this perception, we see that the roles played by the consumer, the manufacturer and the designer should consider the impact of production on the environment and the life cycle of the product. At the moment, fashion goes from fast fashion to the slow fashion when, finally, in addition to monetary goals, greater focus will be on design, quality, product durability and also the environment.